Training Technologies as Means for Forming the Professional Identity of Police Officers during Professional Genesis - O. Y. Shlomin (Law and Safety)
One of the modern technologies for training and developing individuals is a variety of trainings, including professionally-oriented ones. Since the training of modern police officers in higher educational institutions with specific learning conditions should focus on professional self-development of personality, formation and development of professional identity and other necessary personal and professional qualities, the aim of the study was to identify the effectiveness of training procedures on the dynamics of professional identity. Modern concepts of professional genesis, psychological theory of activity and the concept of genetic development of personality became the methodological basis of the study.